A great engineer and inspiring teacher. Issue 1 (March 2020) - Lan, Tien T
This article is presented in remembrance of Professor Mamoru Kawaguchi. He has won a great deal of recognition in China and could be cited as a great engineer. Three projects that have been realized successfully in Tianjin—that is, Yingbin Tower, Tianjin Museum, and Yongle Bridge—are presented. As an inspiring teacher, his remarkable personal quality can be found in three events held in China. The article concludes with his activities in conducting a technical tour of 2016 International Association for Shells and Spatial Structures Symposium and interview of a TV film in 2018.